2010
DOI: 10.1007/s12192-009-0137-6
|View full text |Cite
|
Sign up to set email alerts
|

Caught with their PAMPs down? The extracellular signalling actions of molecular chaperones are not due to microbial contaminants

Abstract: In recent years, it has been hypothesised that a new signalling system may exist in vertebrates in which secreted molecular chaperones form a dynamic continuum between the cellular stress response and corresponding homeostatic physiological mechanisms. This hypothesis seems to be supported by the finding that many molecular chaperones are released from cells and act as extracellular signals for a range of cells. However, this nascent field of biological research seems to suffer from an excessive criticism that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 128 publications
2
74
0
1
Order By: Relevance
“…8), similarly to what has previously been proposed [61]. In line with these observations, we demonstrated that doxorubicin treatment increased the level of p21, a key factor capable of orchestrating cellular senescence [62]. Moreover, the decrease of the intracellular levels of the chaperonin may lead to a decrease in its extracellular release.…”
Section: Discussionsupporting
confidence: 90%
“…8), similarly to what has previously been proposed [61]. In line with these observations, we demonstrated that doxorubicin treatment increased the level of p21, a key factor capable of orchestrating cellular senescence [62]. Moreover, the decrease of the intracellular levels of the chaperonin may lead to a decrease in its extracellular release.…”
Section: Discussionsupporting
confidence: 90%
“…The function of Hsp70 as a potential proinflammatory cytokine capable of inducing innate immunity (9) has long been considered controversial because it has been shown that the presence of endotoxin contaminants was most likely responsible for the observed effects (25). However, Hsp70 purified from nonbacterial origins was shown to be able to moderately stimulate macrophages as well as monocytes (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to playing important roles in maintaining the integrity of cellular proteins and a cell's response to proteotoxic stress, HSPs also function in inflammation, immune signaling, and antigen presentation Henderson et al 2010). The gastric pathogen H. pylori, the primary cause of chronic gastritis, peptic ulcer, MALT, and gastric cancer, has been demonstrated to down-modulate host-cell HSP expression upon infection (Axsen et al 2009;Baek et al 2004;Konturek et al 2001;Pierzchalski et al 2006;Targosz et al 2006;Yeo et al 2004).…”
Section: Discussionmentioning
confidence: 99%